Neural sensitivity to social rejection is associated with inflammatory responses to social stress - Slavich, George M; Way, Baldwin M; Eisenberger, Naomi I; Taylor, Shelley E (Proceedings of the National Academy of Sciences - PNAS, 2010)
Although stress-induced increases in inflammation have been implicated in several major disorders, including cardiovascular disease and depression, the neurocognitive pathways that underlie inflammatory responses to stress remain largely unknown. To examine these processes, we recruited 124 healthy young adult participants to complete a laboratory-based social stressor while markers of inflammatory activity were obtained from oral fluids. A subset of participants (n = 31) later completed an fMRI session in which their neural responses to social rejection were assessed. As predicted, exposure to the laboratory-based social stressor was associated with significant increases in two markers of inflammatory activity, namely a soluble receptor for tumor necrosis factor-alpha (sTNFalphaRII) and interleukin-6 (IL-6). In the neuroimaging subsample, greater increases in sTNFalphaRII (but not IL-6) were associated with greater activity in the dorsal anterior cingulate cortex and anterior insula, brain regions that have previously been associated with processing rejection-related distress and negative affect. These data thus elucidate a neurocognitive pathway that may be involved in potentiated inflammatory responses to acute social stress. As such, they have implications for understanding how social stressors may promote susceptibility to diseases with an inflammatory component.